Postural Stability in Parkinson’s Disease Patients Is Improved after Stochastic Resonance Therapy - Oliver Kaut; Daniel Brenig; Milena Marek; Niels Allert; Ullrich Wüllner (Parkinson's Disease)
Background. Postural instability in Parkinson’s disease (PD) increases the risk of falls and is not improved by pharmacological therapy. Objective. We performed a double-blind, randomized sham-controlled study to test the effects of stochastic resonance (whole body vibration) therapy on postural stability in PD. Methods. Fifty-six PD participants were allocated to either experimental or sham groups. The experimental group received four series of vibration over eight days, with each series consisting of six stimulus trains of 60-second duration using a randomized whole body vibration. Participants allocated to the control group received a sham treatment. Results. Within-group analysis revealed that postural stability in the experimental group improved by 17.5% (p=0.005) comparing experimental and sham groups. The between-group analysis of change after treatment comparing both groups also showed a significant improvement of postural stability (p=0.03). Only in the within-group analysis several items were improved after Bonferroni correction, too, rigor 41.6% (p=0.001), bradykinesia 23.7% (p=0.001), tremor 30.8% (p=0.006), and UPDRSIII sum score 23.9% (p=0.000), but did not reach the level of significance in the between-group analysis. Conclusions. Stochastic resonance therapy significantly enhanced postural stability even in individuals with increased risk of falling. Thus it offers a potential supplementation to canonical treatments of PD.